2010
DOI: 10.1369/jhc.2010.956821
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Serum Amyloid A in Human Ovarian Epithelial Tumors: Implication for a Role in Ovarian Tumorigenesis

Abstract: Serum amyloid A (SAA) is an acute phase protein which is expressed primarily in the liver as a part of the systemic response to various injuries and inflammatory stimuli; its expression in ovarian tumors has not been described. Here, we investigated the expression of SAA in human benign and malignant ovarian epithelial tumors. Non-radioactive in situ hybridization applied on ovarian paraffin tissue sections revealed mostly negative SAA mRNA expression in normal surface epithelium. Expression was increased grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 34 publications
6
55
0
2
Order By: Relevance
“…SAA expression level was already found elevated in HCC patients. (35) Moreover, cancer studies of lung cancer, (36) renal cell cancer, (37) or ovarian carcinoma (38) have implied the potential biomarker role of SAA. Obviously, it is not appropriate to use SAA as an exclusive biomarker for any specific cancer type, whereas it could coordinate with other markers for cancer surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…SAA expression level was already found elevated in HCC patients. (35) Moreover, cancer studies of lung cancer, (36) renal cell cancer, (37) or ovarian carcinoma (38) have implied the potential biomarker role of SAA. Obviously, it is not appropriate to use SAA as an exclusive biomarker for any specific cancer type, whereas it could coordinate with other markers for cancer surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…NOS2 has been reported to be implicated and correlated with various prostatic diseases including PCa (26). Finally, SAA1 has been found to be highly expressed in lung cancer tissue (27) and over-expressed in ovarian carcinoma tissues (28).…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest that ETS-1 represses the expression of the immunity-related genes CD38 and HDAC9, while activating the expression of BCL11A, CRISP3, DMBT1, FGR, NOS2 and SAA1 in PC3 PCa cells. Besides the roles of these genes in the immune response, several have been reported to be involved in various types of cancer, including PCa (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, the precise roles that these genes may play in the network of cellular and molecular mechanisms of antitumor immunology according to current models is not always clear from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, SAA in serum levels were found elevated in a wide range of cancers. SAA is expressed locally in colon carcinoma and also overexpression in endometrial carcinoma and ovarian tumors (49). Breast cancer is one of the most common cancers in women worldwide.…”
Section: Acute-phase Proteins As Tumorigenic Factors or Diseases Indumentioning
confidence: 99%